Price variation in vegetable market: a study on effective supply chain management in Bangladesh - Bhuiyan, Mohammad Anamul Hoque (BRAC University, 2016)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Masters in Procurement and Supply Management, 2015.